1985
DOI: 10.1111/j.1600-0722.1985.tb01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental erosions in relation to lactovegetarian diet

Abstract: – The subjects of this study were 26 lac to vegetarians and their age‐ and sex‐matched controls. Clinical and radiologic examinations were made and samples of wax‐stimulated whole saliva were collected. Dental erosions were recorded and documented with photographs and plaster models. Incipient, moderate and grave erosive defects were observed in 26.9%, 19.2% and 30.8% of the lactovegetarians, respectively. In controls, however, no erosions were observed. When tested by multiple linear regression analysis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
2
13

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 14 publications
6
82
2
13
Order By: Relevance
“…25 Epidemiyolojik çalıĢmalar erozyon ile sirke, turĢu, turunç-gil ve meyve suyu gibi gıdaların tüketimi ara-sında iliĢki olduğunu göstermektedir. 26 Ayrıca asidik yiyecek ve içeceklerin alım sıklığının tüketilen miktardan daha etkili olduğu ve erozyonun ağız hijyeni iyi olan bireylerde daha fazla görüldüğü bildirilmektedir. 27 Jarvinen ve arkadaĢlarının yaptıkları çalıĢmada günde ikiden fazla narenciye, haftada birden fazla sirke veya spor içeceği tüketimi olanlarla erozyon görülme sıklığı arasında iliĢki olduğu belirtilmektedir.…”
Section: Erozyon Ve Di̇yet İli̇şki̇si̇unclassified
“…25 Epidemiyolojik çalıĢmalar erozyon ile sirke, turĢu, turunç-gil ve meyve suyu gibi gıdaların tüketimi ara-sında iliĢki olduğunu göstermektedir. 26 Ayrıca asidik yiyecek ve içeceklerin alım sıklığının tüketilen miktardan daha etkili olduğu ve erozyonun ağız hijyeni iyi olan bireylerde daha fazla görüldüğü bildirilmektedir. 27 Jarvinen ve arkadaĢlarının yaptıkları çalıĢmada günde ikiden fazla narenciye, haftada birden fazla sirke veya spor içeceği tüketimi olanlarla erozyon görülme sıklığı arasında iliĢki olduğu belirtilmektedir.…”
Section: Erozyon Ve Di̇yet İli̇şki̇si̇unclassified
“…Erosion was seen in patients with symptoms of gastric reflux 2,3 and later was recognised in patients with anorexia 4 or bulimia 5 or in patients with unusual dietary habits. 6 In some cases erosion has been recognised as an occupational disease where workers have been exposed to acidic fumes, for example in factories making batteries. 7,8 It is also recognised among wine-tasters 9 (Type 4,5).…”
Section: N B R I E Fmentioning
confidence: 99%
“…Eccles confirmed the importance of these beverages when he reported that they were implicated as aetiological factors in 40% of patients with TSL. 15 A 'healthy' diet may also contain substantial acidic foods [16][17][18] and cause further loss of tooth tissue. Furthermore, the abrasive nature of many of the components of these diets may accelerate TSL.…”
Section: Erosionmentioning
confidence: 99%